2019
DOI: 10.1155/2019/8978021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Prevention Practices of Drug Resistant Tuberculosis in the Eastern Cape Province, South Africa

Abstract: The aim of this study was to assess community members' knowledge and awareness levels, attitudes, and practices of Drug Resistant Tuberculosis. A quantitative descriptive cross sectional study was carried out in the Eastern Cape Province of South Africa. The sample size consisted of four hundred (400) respondents aged 18 years and above on their last birthday who were purposively and conveniently selected from Port Elizabeth area in the Nelson Mandela Municipality. Data were collected using close-ended questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
4
3
Order By: Relevance
“…The present study demonstrated that the likelihood of having good knowledge was 1.3 times higher in those patients who sleep alone in a separate room than respondents who shared a bedroom with his/her family or friends. On the contrary, a study conducted in Yangon Myanmar found that 96.3% of patients [22]. The current findings might be due to a lack of awareness and knowledge about the mode of transmission and ways of prevention of MDR-TB.…”
Section: Discussioncontrasting
confidence: 85%
“…The present study demonstrated that the likelihood of having good knowledge was 1.3 times higher in those patients who sleep alone in a separate room than respondents who shared a bedroom with his/her family or friends. On the contrary, a study conducted in Yangon Myanmar found that 96.3% of patients [22]. The current findings might be due to a lack of awareness and knowledge about the mode of transmission and ways of prevention of MDR-TB.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast, a previous study on healthcare providers' attitudes towards TB in a pastoralist community in Ethiopia reported only about 44.4% of HCWs had favourable attitudes toward TB control and prevention [ 32 ]. In contrast to our study, a marginally high unfavourable attitude score (76.5%) was reported from a study conducted on attitudes toward drug-resistant TB in the Eastern Cape Province of South Africa [ 33 ], though the target population group of the study was the general community members. The similarity between the present study and the previous studies might be due to the similarity of the target population.…”
Section: Resultscontrasting
confidence: 99%
“…Knowledge about TB in Equatorial Guinea’s general population is low. Only one third of respondents had a high TB knowledge score, a percentage much lower than the knowledge found in other KAP studies in Africa [ 11 , 16 , 27 , 28 , 29 ]. Meanwhile, Guinean caregivers with a TB case in the family have better knowledge than the rest of the population.…”
Section: Discussioncontrasting
confidence: 67%